Fluorite type high-entropy oxide ceramic precursor and ceramic powder thereof and preparation method of fluorite type high-entropy oxide ceramic precursor

The preparation of A2B2O7 high-entropy oxide ceramic powders by liquid-phase polymer precursor method solves the problems of uneven powder structure grinding and insufficient solid solution reaction in the existing methods. The obtained ceramic block has low thermal conductivity and good high temperature stability, which significantly improves the performance stability of the coating.

CN119591402APending Publication Date: 2025-03-11AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411725587.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing synthetic methods of A2B2O7 type oxide ceramics have problems such as uneven powder structure grinding, insufficient solid solution reaction, increased temperature, and increased unreacted crystals and impurities, resulting in a degradation of the performance of the coating during use.

Method used

Using the liquid-phase polymer precursor method, an aqueous solution is formed in deionized water by hydrates of lanthanum nitrate, cerium nitrate, yttrium nitrate and erbium nitrate, and a chelating agent and alkaline reagent are added for complexing and acid-base neutralization reaction. The complex powder is obtained by filtration, and stirring and reacting with the alkoxides of elements such as Zr, Hf, Ta, Ti and other elements to form an A2B2O7 high-entropy oxide ceramic precursor solution, and then cracking in an air atmosphere to form a high-entropy oxide ceramic powder.

Benefits of technology

The high-entropy oxide ceramic blocks produced by this method have low thermal conductivity and good high-temperature stability. After 1600°C high-temperature treatment for 100 hours, they still have a single-phase solid solution structure, which significantly improves the performance stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591402A_ABST
    Figure CN119591402A_ABST
Patent Text Reader

Abstract

The invention relates to a fluorite type high-entropy oxide ceramic precursor, a fluorite type high-entropy oxide ceramic powder and a preparation method thereof. The preparation method comprises the following steps: placing hydrates of at least two of lanthanum nitrate, cerium nitrate, yttrium nitrate and erbium nitrate into deionized water to obtain an aqueous solution; adding a chelating agent into the aqueous solution for complexing reaction; adding ammonia water or triethylamine and the like into the solution to carry out acid-base neutralization reaction, and filtering to obtain complex powder of La, Ce, Y and Er; adding the complex powder into alkoxides of at least two of Zr, Hf, Ta and Ti, stirring for reaction, and then hydrolyzing to obtain an A2B2O7 high-entropy oxide ceramic precursor solution; and cracking in an air atmosphere to form the A2B2O7 powder. The invention also relates to a ceramic block material prepared from the fluorite type high-entropy oxide powder prepared by the method. The high-entropy oxide block prepared by the invention has relatively low thermal conductivity and good high-temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerospace materials, and in particular to a fluorite-type high-entropy oxide ceramic precursor and a ceramic powder thereof and a preparation method thereof. Background Art

[0002] In order to improve the high temperature and corrosion resistance of gas turbine blades and rocket engines, NASA-Lewis Research Center proposed the concept of thermal barrier coating as early as the 1950s, and passed the first ground test in the mid-1970s. Thermal barrier coatings are mainly used on engine alloy turbine blades to produce a large temperature drop (about 170°C) between high-temperature combustion gas and matrix alloy brackets. The system commonly used in thermal barrier coatings is yttria-stabilized zirconia (YSZ), which has the characteristics of high melting point (Tm=2700°C) and low thermal conductivity (2.3W / m·K). For thermal barrier coatings, lower thermal conductivity and high temperature stability are two key technical indicators. The long-term high-temperature sintering of YSZ material at 1200°C will cause part of the yttria-stabilized zirconia system to form high yttria phase and low yttria phase, thereby losing the function of stabilizing the zirconia crystal phase transformation during the cooling process, resulting in cracking and failure of the coating. Therefore, fluorite-structured A2B2O7-type oxides have gradually been developed into a research hotspot due to their high-temperature stability. Moreover, by increasing the entropy of the A and B positions, the internal defects of the crystal can be increased, causing phonon scattering and further reducing the thermal conductivity of the material.

[0003] At present, the synthesis method of A2B2O7 type oxide is mainly the traditional solid phase sintering method, that is, using Zr, Hf, La, Yb and other unit oxide powders as raw materials, ball milling and mixing evenly, hot pressing at high temperature (>1600℃), and obtaining through solid solution reaction. This method is simple and easy, and has low requirements for raw materials and equipment. However, since the raw material is a powder structure, the minimum particle size after grinding is still about 1μm, and the mixing is uneven, resulting in insufficient solid solution reaction. In order to promote the solid solution reaction, it is usually necessary to increase the temperature to above 1600℃, but the increase in temperature will cause the uncontrolled increase of the unreacted crystal particles, further increasing the difficulty of the solid solution reaction, and finally forming an impurity second phase; and the grinding process of the solid phase sintering method will introduce impurities due to equipment wear, and the obtained high entropy oxide usually contains a small amount of impurities, resulting in the degradation of the performance of the later coating during use. The liquid phase polymer precursor method is an important method for developing high-entropy ceramics. The product ratio can be accurately controlled by adding elements. By constructing polymers containing target elements, the elements can be distributed at the molecular level. High-entropy oxide ceramics can be formed at a relatively low temperature (<1000°C). This "bottom-up" synthesis method makes the element ratio and the degree of ceramic crystallization controllable, which is conducive to obtaining highly active nanopowders. Ceramic blocks can be prepared by hot pressing at low temperatures, and the product purity is relatively high.

[0004] The A position of A2B2O7 type oxides is usually a rare earth element, and the B position is usually a transition metal element. Both elements have high coordination numbers and high activity. In the preparation process of polymer precursors in the liquid phase polymer precursor method, gelation or air oxidation to inorganic oxides is prone to occur. Therefore, how to prepare polymer precursors containing the above elements has become a problem that needs to be solved. Summary of the invention

[0005] The invention provides a fluorite-type high-entropy oxide ceramic precursor and a ceramic powder thereof and a preparation method thereof, as well as a ceramic block material with excellent mechanical properties prepared by the method.

[0006] In a first aspect, the present invention provides a method for preparing a fluorite-type high entropy oxide ceramic precursor and a ceramic powder thereof, the method comprising the following steps:

[0007] placing hydrates of at least two of lanthanum nitrate, cerium nitrate, yttrium nitrate, and erbium nitrate in deionized water to obtain an aqueous solution;

[0008] Adding a chelating agent into the aqueous solution to carry out a complexation reaction;

[0009] Adding an alkaline reagent into the solution to carry out an acid-base neutralization reaction, and filtering to obtain a complex powder of La, Ce, Y, and Er;

[0010] The complex powder is added to at least two alcohol salts of Zr, Hf, Ta, and Ti, stirred for reaction, and then hydrolyzed to obtain A2B2O7 (A=La x1 , Y x2 、Ce x3 , Er x4 ; x1+x2+x3+x4=1, B=Zr y1 , Hf y2 、 y3 、Ti y4 ; y1+y2+y3+y4=1) high entropy oxide ceramic precursor solution;

[0011] The A2B2O7 high entropy oxide ceramic precursor solution is pyrolyzed in an air atmosphere to form A2B2O7 (A=La x1 , Y x2 、Ce x3 , Er x4 ; x1+x2+x3+x4=1, B=Zr y1 , Hf y2 、 y3 、Ti y4 ; y1+y2+y3+y4=1) powder, that is, high entropy oxide ceramic powder.

[0012] In some preferred embodiments, the x1:x2:x3:x4=1:(0.5~2):(0.5~2):(0.5~2), preferably 1:(0.5~1):(0.5~1):(0.5~1).

[0013] In some other preferred embodiments, the mass of the aqueous solution is 3 to 8 times, preferably 6 to 7 times, the mass of the raw material, wherein the raw material is a hydrate of at least two of lanthanum nitrate, cerium nitrate, yttrium nitrate and erbium nitrate.

[0014] In other preferred embodiments, the chelating agent includes acetylacetone, acetic acid, ethylenediamine, etc., and acetic acid is preferably used as the chelating agent.

[0015] In other preferred embodiments, the amount of acetic acid (HAc) used (molar ratio) is (x1+x2+x3+x4): HAc=1:(1-2), preferably 1:(1-1.5).

[0016] In other preferred embodiments, the alkaline reagent used in the acid-base neutralization reaction is ammonia water or triethylamine, and ammonia water is preferred for the acid-base neutralization reaction.

[0017] In other preferred embodiments, the amount of ammonia water or triethylamine used is the molar ratio of (x1+x2+x3+x4): NH3·H2O=1:(1~2), or (x1+x2+x3+x4): triethylamine=1:(1~2), preferably 1:(1~1.5).

[0018] In other preferred embodiments, (x1+x2+x3+x4):(y1:y2:y3:y4)=1:1.

[0019] In other preferred embodiments, y1:y2:y3:y4=1:(0.5~2):(0.5~2):(0.5~2), preferably 1:(0.5~1):(0.5~1):(0.5~1).

[0020] In other preferred embodiments, the stirring reaction time is 0.5 to 3 hours, preferably 1 to 2 hours.

[0021] In other preferred embodiments, the stirring reaction temperature is RT to 150°C, preferably 50 to 80°C.

[0022] In other preferred embodiments, the amount of water used for hydrolysis is a molar ratio of (y1+y2+y3+y4): H2O=1:(0.5-2), preferably 1:(0.6-1.5).

[0023] In other preferred embodiments, the hydrolysis temperature is RT to 150°C, preferably 50 to 80°C.

[0024] In other preferred embodiments, the cracking temperature is 600-1200°C, preferably 800-1000°C.

[0025] In a second aspect, the present invention provides a high entropy oxide ceramic powder prepared according to the method described in the first aspect of the present invention.

[0026] The present invention provides a high entropy oxide ceramic block made from the high entropy oxide ceramic powder according to the second aspect of the present invention in a third aspect. The high entropy oxide ceramic block is obtained by hot pressing and sintering the high entropy oxide ceramic powder.

[0027] The high entropy oxide ceramic block prepared by the method of the present invention has a relatively low thermal conductivity. Preferably, the thermal conductivity of the high entropy oxide ceramic block is 0.95 to 1.58 W / (m·K), preferably 1.02 to 1.39 W / (m·K).

[0028] The high entropy oxide ceramic block prepared by the method of the present invention has good high-temperature stability. After being subjected to high-temperature treatment at 1600° C. for a total of 100 hours, the product still has a single-phase solid solution structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope photograph of the (LaYCeEr)2(ZrHfTaTi)2O7 high entropy oxide ceramic prepared in Example 1.

[0030] Figure 2 This is the XRD pattern of the (LaYCeEr)2(ZrHfTaTi)2O7 high entropy oxide ceramic prepared in Example 1.

[0031] Figure 3 This is the XRD diagram of the (LaYCeEr)2(ZrHfTaTi)2O7 high entropy oxide ceramic prepared in Example 1 after being subjected to a high temperature treatment at 1600°C for a total of 100 hours. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] A first aspect of the present invention provides a method for preparing a high entropy oxide ceramic, the method comprising the following steps:

[0034] 1) placing hydrates of at least two of lanthanum nitrate, cerium nitrate, yttrium nitrate and erbium nitrate in deionized water to obtain an aqueous solution;

[0035] 2) adding a chelating agent into the aqueous solution to carry out a complexing reaction;

[0036] 3) adding ammonia water or triethylamine into the solution to carry out acid-base neutralization reaction, and filtering to obtain the complex powder of La, Ce, Y, and Er;

[0037] 4) Add the complex powder to at least two alcohol salts of Zr, Hf, Ta, and Ti, stir the reaction, and then hydrolyze to obtain A2B2O7 (A=La x1 , Y x2 、Ce x3 , Er x4 At least two of the following: x1+x2+x3+x4=1, B=Zr y1 , Hf y2 、 y3 、Ti y4 At least two of the following: y1+y2+y3+y4=1) a high entropy oxide ceramic precursor solution;

[0038] 5) Cracking in air atmosphere to form A2B2O7 (A=La x1 , Y x2 、Ce x3 , Er x4 ; x1+x2+x3+x4=1, B=Zr y1 , Hf y2 、 y3 、Ti y4 ;y1+y2+y3+y4=1) powder.

[0039] In some preferred embodiments, the x1:x2:x3:x4=1:(0.5-2):(0.5-2):(0.5-2), preferably 1:(0.5-1):(0.5-1):(0.5-1), for example, x1:x2:x3:x4=1:0.5:0.5:0.5, x1:x2:x3:x4=1:0.6:0.6:0.6, x1:x2:x3:x4=1:0.7:0.7:0.7, x1:x2:x3:x4=1:0.8:0.8:0 .8, x1:x2:x3:x4=1:0.9:0.9:0.9, x1:x2:x3:x4=1:1.0:1.0:1.0, x1:x2:x3:x4=1:0.5:0.6:0.6, x1:x2:x3:x4=1:0.6:0.7:0.7, x1:x2:x3:x4=1:0.7:0.8:0.9, x1:x2:x3:x4=1:1.0:0.5:0.6, x1:x2:x3:x4=1:1.0:0.8:0.9.

[0040] In other preferred embodiments, the mass of the aqueous solution is 3 to 8 times, preferably 6 to 7 times, such as 6 times, 6.5 times, or 7 times the mass of the raw material.

[0041] In other preferred embodiments, the chelating agent includes acetylacetone, acetic acid, ethylenediamine, etc., and acetic acid is preferably used as the chelating agent.

[0042] In other preferred embodiments, the amount of acetic acid used is (x1+x2+x3+x4):HAc=1:(1-2), preferably 1:(1-1.5), for example 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.20, 1:1.25, 1:1.30, 1:1.35, 1:1.40, 1:1.45, 1:1.5.

[0043] In other preferred embodiments, the acid-base neutralization reaction is preferably carried out with aqueous ammonia.

[0044] In other preferred embodiments, the amount of ammonia water or triethylamine used is the molar ratio of (x1+x2+x3+x4): NH3·H2O (or triethylamine) = 1:(1-2), preferably 1:(1-1.5), for example 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.20, 1:1.25, 1:1.30, 1:1.35, 1:1.40, 1:1.45, 1:1.5.

[0045] In other preferred embodiments, (x1+x2+x3+x4):(y1:y2:y3:y4)=1:1.

[0046] In other preferred embodiments, y1:y2:y3:y4=1:(0.5-2):(0.5-2):(0.5-2), preferably 1:(0.5-1):(0.5-1):(0.5-1), for example, y1:y2:y3:y4=1:0.5:0.5:0.5, y1:y2:y3:y4=1:1:0.5:0.5, y1:y2:y3:y4=1:0.5:1:0.5, y1:y2:y3:y4=1:0.8:0.8:0.8, y1:y2:y3:y4=1:0.9:0.9:0.9, y1:y2:y3:y4=1:1.0:1.0:1.0, y1:y2:y3:y4=1:0.5:0.6:0.6, y1:y2:y3:y4=1 :0.6:0.7:0.7, y1:y2:y3:y4=1:0.7:0.8:0.9, y1:y2:y3:y4=1:1.0:0.5:0.6, y1:y2:y3:y4=1:1.0:0.8:0.9.

[0047] In other preferred embodiments, the stirring reaction time is 0.5 to 3 h, preferably 1 to 2 h, for example 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h.

[0048] In other preferred embodiments, the stirring reaction temperature is RT to 150°C, preferably 50 to 80°C, for example 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C.

[0049] In other preferred embodiments, the amount of water used for hydrolysis is a substance molar ratio of (y1+y2+y3+y4):H2O=1:(0.5-2), preferably 1:(0.6-1.5), for example (y1+y2+y3+y4):H2O=1:0.6, (y1+y2+y3+y4):nH2O=1:0.65, (y1+y2+y3+y4):H2 O=1:0.7,(y1+y2+y3+y4):H2O=1:0.75,(y1+y2+y3+y4):H2O=1:0.8,(y1+y2+y3+ y4): H2O=1: 0.85, (y1+y2+y3+y4): H2O=1: 0.9, (y1+y2+y3+y4): H2O=1: 0.95, (y1+ y2+y3+y4): H2O=1:1.0, (y1+y2+y3+y4): H2O=1:1.05, (y1+y2+y3+y4): H2O=1:1. 10, (y1+y2+y3+y4): H2O=1: 1.15, (y1+y2+y3+y4): H2O=1: 1.20, (y1+y2+y3+y4): H 2O=1:1.25,(y1+y2+y3+y4):H2O=1:1.30,(y1+y2+y3+y4):H2O=1:1.35,(y1+y2+ y3+y4): H2O=1:1.40, (y1+y2+y3+y4): H2O=1:1.45, (y1+y2+y3+y4): H2O=1:1.50.

[0050] In other preferred embodiments, the hydrolysis temperature is RT to 150°C, preferably 50 to 80°C, for example 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C.

[0051] In other preferred embodiments, the cracking reaction temperature is 600-1200°C, preferably 800-1000°C, for example 800°C, 850°C, 900°C, 950°C, 1000°C.

[0052] In a second aspect, the present invention provides a high entropy oxide ceramic powder prepared according to the method described in the first aspect of the present invention.

[0053] In a third aspect, the present invention provides a high entropy oxide ceramic block made from the high entropy oxide ceramic powder described in the second aspect of the present invention.

[0054] The high entropy oxide ceramic block prepared by the method of the present invention has a low thermal conductivity. Preferably, the thermal conductivity of the high entropy oxide ceramic block is 0.95 to 1.58 W / (m·K), preferably 1.02 to 1.39 W / (m·K), for example, 1.02 W / (m·K), 1.10 W / (m·K), 1.14 W / (m·K), 1.21 W / (m·K), 1.25 W / (m·K), 1.33 W / (m·K), 1.35 W / (m·K), 1.39 W / (m·K).

[0055] The high entropy oxide ceramic block prepared by the method of the present invention has good high-temperature stability. After being subjected to high-temperature treatment at 1600° C. for a total of 100 hours, the product still has a single-phase solid solution structure.

[0056] The present invention will be further described below in conjunction with specific examples. However, it should be understood that these examples are only used to illustrate the present invention and do not constitute a limitation of the scope of the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0057] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified. All percentages and parts are by weight unless otherwise specified.

[0058] In the following examples, except for vacuum impregnation, other process steps are carried out under the protection of argon atmosphere.

[0059] Embodiment 1:

[0060] (1) Preparation of high entropy oxide ceramic powder: La nitrate, cerium nitrate, yttrium nitrate, erbium nitrate hydrates are added in a ratio of x1:x2:x3:x4=1:1.0:1.0:1.0, and placed in deionized water, the amount of water added is 6.5 times the total amount of nitrate, to obtain an aqueous solution. Acetic acid is added in a ratio of (x1+x2+x3+x4):HAc=1:1.05 for complexation, and ammonia water is added in a ratio of (x1+x2+x3+x4):NH3·H2O=1:1.05 for acid-base neutralization reaction, and the complex powders of La, Ce, Y, and Er are obtained by filtration. The complex powder was added to the alcohol salts of Zr, Hf, Ta and Ti according to (x1+x2+x3+x4):(y1:y2:y3:y4)=1:1, y1:y2:y3:y4=1:1:1:1, the stirring reaction time was 1.5h, and the reaction temperature was 55°C. Subsequently, it was hydrolyzed according to the ratio of (y1+y2+y3+y4):H2O=1:0.7, and the hydrolysis temperature was 60°C to obtain (LaYCeEr)2(ZrHfTaTi)2O7 high entropy oxide ceramic precursor solution; it was pyrolyzed at 900°C in an air atmosphere to form (LaYCeEr)2(ZrHfTaTi)2O7 powder. Its microscopic morphology is as follows Figure 1 As shown, the XRD pattern is Figure 2 shown.

[0061] (2) Thermal conductivity test: The high entropy oxide powder was hot pressed into a specimen for testing thermal conductivity. After testing, the thermal conductivity was 1.08 W / (m·K).

[0062] (3) High temperature thermal stability test: After the high entropy oxide powder was subjected to high temperature treatment in a muffle furnace in an air atmosphere at 1600°C for a total of 100 hours, the product was still a single-phase solid solution structure after XRD detection. The XRD pattern is shown in the figure below: Figure 3 shown.

[0063] Embodiment 2:

[0064] (1) Preparation of high entropy oxide ceramic powder: La nitrate, cerium nitrate, yttrium nitrate, and erbium nitrate hydrates were added in a ratio of x1:x2:x3:x4=1:1.0:1.0:1.0, and placed in deionized water, where the amount of water added was 7 times the total amount of nitrate, to obtain an aqueous solution. Acetic acid was added in a ratio of (x1+x2+x3+x4):HAc=1:1.30 for complexation, and ammonia was added in a ratio of (x1+x2+x3+x4):NH3·H2O=1:1.25 for acid-base neutralization reaction, and the complex powders of La, Ce, Y, and Er were obtained by filtration. The complex powder was added to the alcohol salts of Zr, Hf, Ta and Ti according to (x1+x2+x3+x4):(y1:y2:y3:y4)=1:1, y1:y2:y3:y4=1:1:0.5:0.5, stirred for 2 hours, and the reaction temperature was 60°C. Then, it was hydrolyzed according to the ratio of (y1+y2+y3+y4):H2O=1:1.35, and the hydrolysis temperature was 75°C to obtain (LaYCeEr)2(Zr 0.33 Hf 0.33 Ta 0.17 Ti 0.17 )2O7 high entropy oxide ceramic precursor solution; pyrolysis at 850℃ in air atmosphere to form (LaYCeEr)2(Zr 0.33 Hf 0.33 Ta 0.17 Ti 0.17 )2O7 powder.

[0065] (2) Thermal conductivity test: The high entropy oxide powder was hot pressed into a specimen for testing thermal conductivity. After testing, the thermal conductivity was 1.12 W / (m·K).

[0066] (3) High-temperature thermal stability test: After the high-entropy oxide powder was subjected to high-temperature treatment in a muffle furnace in an air atmosphere at 1600°C for a total of 100 h, the product was still a single-phase solid solution structure after XRD detection.

[0067] Embodiment 3:

[0068] (1) Preparation of high entropy oxide ceramic powder: La nitrate, cerium nitrate, yttrium nitrate, and erbium nitrate hydrates were added in a ratio of x1:x2:x3:x4=1:1:1:1, and placed in deionized water, where the amount of water added was 7 times the total amount of nitrate, to obtain an aqueous solution. Acetic acid was added in a ratio of (x1+x2+x3+x4):HAc=1:1.30 for complexation, and ammonia was added in a ratio of (x1+x2+x3+x4):NH3·H2O=1:1.25 for acid-base neutralization reaction, and the complex powders of La, Ce, Y, and Er were obtained by filtration. The complex powder was added to the alcohol salts of Zr, Hf, Ta and Ti according to (x1+x2+x3+x4):(y1:y2:y3:y4)=1:1, y1:y2:y3:y4=1:0.5:1:0.5, stirred for 2 hours, and the reaction temperature was 60°C. Then, it was hydrolyzed according to the ratio of (y1+y2+y3+y4):H2O=1:1.35, and the hydrolysis temperature was 50°C to obtain (LaYCeEr)2(Zr 0.33 Hf 0.17 Ta 0.33 Ti 0.17 )2O7 high entropy oxide ceramic precursor solution; pyrolysis at 850℃ in air atmosphere to form (LaYCeEr)2(Zr 0.33 Hf 0.17 Ta 0.33 Ti 0.17 )2O7 powder.

[0069] (2) Thermal conductivity test: The high entropy oxide powder was hot pressed into a specimen for testing thermal conductivity. After testing, the thermal conductivity was 1.24W / (m·K).

[0070] (3) High-temperature thermal stability test: After the high-entropy oxide powder was subjected to high-temperature treatment in a muffle furnace in an air atmosphere at 1600°C for a total of 100 h, the product was still a single-phase solid solution structure after XRD detection.

[0071] Comparative Example 1:

[0072] (1) Compared with Example 1, the hydrolysis temperature was changed to 25° C., and other conditions were the same. The XRD result of the pyrolyzed ceramic product was a multiphase product, not a single-phase high entropy oxide solid solution.

[0073] (2) Thermal conductivity test: The high entropy oxide powder was hot pressed into a specimen for testing thermal conductivity. After testing, the thermal conductivity was 3.08 W / (m·K).

[0074] (3) High-temperature thermal stability test: After the high-entropy oxide powder was subjected to high-temperature treatment in a muffle furnace with air atmosphere at 1600°C for a total of 100 h, XRD analysis of the product showed that the type of phase did not change.

[0075] Comparative Example 2:

[0076] (1) Compared with Example 1, the ratio of water in the hydrolysis reaction was adjusted to (y1+y2+y3+y4): H2O=1:3, and other conditions were the same. The XRD result of the pyrolyzed ceramic product was a multiphase product, not a single-phase high entropy oxide solid solution.

[0077] (2) Thermal conductivity test: The high entropy oxide powder was hot pressed into a specimen for testing thermal conductivity. After testing, the thermal conductivity was 6.79 W / (m·K).

[0078] (3) High-temperature thermal stability test: After the high-entropy oxide powder was subjected to high-temperature treatment in a muffle furnace with air atmosphere at 1600°C for a total of 100 h, XRD analysis of the product showed that the type of phase did not change.

[0079] Comparative Example 3:

[0080] (1) Compared with Example 1, the stirring reaction time was changed to 5 h, and other conditions were the same. The XRD result of the pyrolyzed ceramic product was a multiphase product, not a single-phase high entropy oxide solid solution.

[0081] (2) Thermal conductivity test: The high entropy oxide powder was hot pressed into a specimen for testing thermal conductivity. After testing, the thermal conductivity was 5.84 W / (m·K).

[0082] (3) High-temperature thermal stability test: After the high-entropy oxide powder was subjected to high-temperature treatment at 1600°C in an air atmosphere in a muffle furnace for a total of 100 h, XRD analysis of the product showed that the type of phase had changed.

[0083] The properties of the composite materials prepared in the above-mentioned embodiments and comparative examples are shown in Table 1. The high-entropy ceramic-based composite material prepared by the method of the present invention has good mechanical properties.

[0084] Table 1

[0085]

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a fluorite-type high entropy oxide ceramic precursor and a ceramic powder thereof, characterized in that: The steps include: placing hydrates of at least two of lanthanum nitrate, cerium nitrate, yttrium nitrate, and erbium nitrate in deionized water to obtain an aqueous solution; Adding a chelating agent into the aqueous solution to carry out a complexation reaction; Adding an alkaline reagent into the solution to carry out an acid-base neutralization reaction, and filtering to obtain a complex powder of La, Ce, Y, and Er; The complex powder is added to at least two alcohol salts of Zr, Hf, Ta, and Ti, stirred for reaction, and then hydrolyzed to obtain an A2B2O7 high entropy oxide ceramic precursor solution, wherein A=La x1 , Y x2 、Ce x3 , Er x4 ; x1+x2+x3+x4=1, <h2 style=";text-align:left;direction:ltr">B=Zr<h2 style=";text-align:left;direction:ltr"> y1 <h2 style=";text-align:left;direction:ltr"> Hf<h2 style=";text-align:left;direction:ltr"> y2 <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> y3 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> y4 <h2 style=";text-align:left;direction:ltr"> (y1+y2+y3+y4) = 1 The A2B2O7 high entropy oxide ceramic precursor solution is cracked in an air atmosphere to form A2B2O7 powder, namely, high entropy oxide ceramic powder.

2. The preparation method according to claim 1, characterized in that x1:x2:x3:x4=1:(0.5-2):(0.5-2): (0.5~2)。 3. The preparation method according to claim 1, characterized in that: The mass of the aqueous solution is 3 to 8 times the mass of the hydrate of at least two of the lanthanum nitrate, cerium nitrate, yttrium nitrate and erbium nitrate.

4. The preparation method according to claim 1, characterized in that: The chelating agent includes acetylacetone or acetic acid or ethylenediamine; The amount of acetic acid used is the molar ratio of (x1+x2+x3+x4): acetic acid = 1: (1-2).

5. The preparation method according to claim 1, characterized in that: The alkaline reagent is ammonia water or triethylamine; the usage of ammonia water or triethylamine is the molar ratio of (x1+x2+x3+x4): ammonia water or triethylamine=1:(1-2).

6. The preparation method according to claim 1, characterized in that: (x1+x2+x3+x4): (y1:y2:y3:y4)=1:1; y1:y2:y3:y4=1: (0.5~2): (0.5~2): (0.5~2).

7. The preparation method according to claim 1, characterized in that: The stirring reaction time is 0.5 to 3 hours, and the stirring reaction temperature is RT to 150° C.; the amount of water used in the hydrolysis is the molar ratio of (y1+y2+y3+y4): H2O=1:(0.5 to 2); The temperature of the hydrolysis is RT-150°C; the temperature of the cracking is 600-1200°C.

8. High entropy oxide ceramic powder prepared according to the method according to any one of claims 1 to 7.

9. A high entropy oxide ceramic block, characterized in that: The high entropy oxide ceramic block is made by hot pressing and sintering the high entropy oxide ceramic powder according to claim 8.

10. The high entropy oxide ceramic block according to claim 9, characterized in that: The thermal conductivity of the high entropy oxide ceramic block is 0.95-1.58 W / (m·K); the high entropy oxide ceramic block has good high-temperature stability, and after being subjected to high-temperature treatment at 1600° C. for a total of 100 hours, the product still has a single-phase solid solution structure.